Party solidarity, exclusivity and inter-party relationships in Ireland, 1922-1977 - evidence of transfers - Gallagher, Michael (Economic & Social Studies, 1978)
This paper presents an analysis of the transfer of lower preference votes at Irish general elections between 1922 and 1977, illustrating some features of the main Irish parties and of the changing relationships between them. Evidence is found to support the view that Fianna Fail has always been the best organised party, and it is also suggested that a significant proportion of the electorate is not fully aware of the power afforded to it by the electoral system. The construction of a series of alliances in the 1920s and early 1930s, and their loosening in the late 1930s, is traced.
Keywords: Electoral behaviour - Ireland; Political parties - Ireland